Impact of Extracapsular Lymph Node Involvement After Neoadjuvant Chemoradiation Therapy Followed by Surgery in Carcinoma of the Esophagus: A Multicenter Study. Issue 6 (December 2018) - Depypere, Lieven P.; Moons, Johnny; Mariette, Christophe; D'Journo, Xavier B.; Thomas, Pascal A.; Hölscher, Arnulf H.; Bollschweiler, Elfriede; van Berge-Henegouwen, Mark I.; Van Lanschot, Jan J. B.; Lerut, Toni E. M. R.; Nafteux, Philippe R.
Abstract : Objectives: The current study aims to examine the impact of extracapsular lymph node involvement (EC-LNI) on survival for both esophageal adenocarcinoma (AC) and squamous cell carcinoma (SCC) treated with neoadjuvant chemoradiation therapy (nCRT) followed by surgery. Background: Studies have demonstrated the negative prognostic value of EC-LNI in primary surgery, but its impact after nCRT remains unclear. Methods: From the databases of 6 European high-volume centers 1505 patients with R0 resections were withheld. Oncologic variables, including ypT, ypN, number of positive lymph nodes, and lymph node capsular status: EC-LNI and intracapsular lymph node involvement (IC-LNI), were examined. Statistical analysis was performed by Cox proportional hazards modeling. Results: In SCC 182 patients (31.6%) had positive lymph nodes, of whom 60 (33.0%) showed EC-LNI. In AC 391 patients (42.1%) had positive lymph nodes, of whom 147 (37.6%) showed EC-LNI. Overall 5-year survival (O5YS) in SCC was 42.0%. Presence of EC-LNI meant a significantly worse O5YS than IC-LNI or pN0 (10.6%, 39.5%, and 47.4%, respectively; P < 0.05). O5YS in AC was 41.2%. No significant difference was observed between EC-LNI and IC-LNI ( P = 0.322). In the multivariate analysis, among the examined possible prognosticators, presence of EC-LNI showed the highest hazard ratio (2.29, confidence interval: 1.52–3.47) as an independent prognosticator for overall survival in SCC, but it was not in AC. Conclusions: Based on this international multicenter study, the presence of EC-LNI after nCRT is at least as important as N-stage for survival and EC-LNI is the strongest prognosticator for overall survival in SCC but not in AC. Abstract : Supplemental Digital Content is available in the text